SARS-CoV-2 Screening Testing Programs for Safe In-person Learning in K–12 Schools. Issue 2 (22nd November 2022) - Kalu, Ibukunoluwa C; Zimmerman, Kanecia O; Goldman, Jennifer L; Keener Mast, Dana; Blakemore, Ashley M; Moorthy, Ganga; Boutzoukas, Angelique E; Campbell, Melissa M; Uthappa, Diya; DeLaRosa, Jesse; Potts, Jessica M; Edwards, Laura J; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) screening testing is a recommended mitigation strategy for schools, although few descriptions of program implementation are available. Methods: Kindergarten through 12th grade (K–12) students and staff practicing universal masking during the delta and omicron variant waves from five schools in Durham, North Carolina and eight schools in Kansas City, Missouri participated; Durham's program was structured as a public health initiative facilitated by school staff, and Kansas City's as a research study facilitated by a research team. Tests included school-based rapid antigen or polymerase chain reaction testing, at-home rapid antigen testing, and off-site nucleic acid amplification testing. Results: We performed nearly 5700 screening tests on more than 1600 K–12 school students and staff members. The total cost for the Durham testing program in 5 public charter K–12 schools, each with 500–1000 students, was $246 587 and approximately 752 h per semester; cost per test was $70 and cost per positive result was $7076. The total cost for the Kansas City program in eight public K–12 schools was $292 591 and required approximately 537 h in personnel time for school-based testing; cost per test was $132 and cost per positive result was $4818. SARS-CoV-2 positivity rates were generally lower (0–16.16%) than rates in the community (2.7–36.47%) throughout all testing weeks. Conclusions and Relevance: Voluntary screening testing programs in K–12 schools are costly and rarely detect asymptomatic positive persons, particularly in universally masked settings. Clinical Trial Registration: NCT04831866. Abstract : We found that school-based SARS-CoV-2 screening testing in K–12 schools is costly and burdensome for personnel. Targeted testing such as diagnostic testing, test-to-stay, or test-to-play may provide better value, particularly when test supplies or personnel are limited.